Dietary behaviour among adults in Northern Ghana: a polytomous logistic regression model approach - Kwame Opare-Asamoah; Daniel Edem Kpewou; Jerry Xola Sosu; Vicentia Esinam Degbey; Ezekiel Kofi Vicar; Julius T Dongdem; Saeed F. Majeed; Kwadwo Fosu Antwi (The South African Journal of Clinical Nutrition)
Objectives: This study determined the predictors of dietary behaviour among adults living in an urban and rural location in northern Ghana.Design: A cross-sectional study.Setting: An urban and rural settlement in the Northern Region of Ghana.Outcome measures: Dietary behaviour levels and their predictors.Subjects: Adults aged ≥ 18 residing in the Tamale Metropolis and the Tolon District of the Northern Region of Ghana.Results: The median age (25th–75th percentile) of all the respondents was 31 (25–39) years, with 44.8% (358) of the respondents aged 20–30 years. There was no statistically significant difference in the respondents’ ages in the two study areas. The median body mass index (BMI) (25th–75th percentile) was 22.0 (20.4–24.0) kg/m2 and did not differ significantly (p-value = 0.23) across the two study areas. Most (74.8%; 598) of the respondents were of normal nutritional status, with half (51.6%) exhibiting good dietary behaviour. Being married (OR = 0.64, p = 0.04) reduces the odds of being at higher dietary behaviour levels. Conversely, being employed (OR  = 1.83, p = 0.003) and aged 50–60 years (OR = 2.80, p = 0.05) increases the odds of being in the higher dietary behaviour categories according to the partially proportional odds model (PPOM). These relationships come with various marginal effects. The relationship between the place of residence of participants and dietary behaviour levels is bidirectional at different dietary levels.Conclusions: This study revealed a complex relationship between dietary behaviour levels and their predictors. This relationship should be considered during interventional and further investigations into dietary behaviours.